2020
DOI: 10.1371/journal.pgen.1009297
|View full text |Cite
|
Sign up to set email alerts
|

Dis3L2 regulates cell proliferation and tissue growth through a conserved mechanism

Abstract: Dis3L2 is a highly conserved 3’-5’ exoribonuclease which is mutated in the human overgrowth disorders Perlman syndrome and Wilms’ tumour of the kidney. Using Drosophila melanogaster as a model system, we have generated a new dis3L2 null mutant together with wild-type and nuclease-dead genetic lines in Drosophila to demonstrate that the catalytic activity of Dis3L2 is required to control cell proliferation. To understand the cellular pathways regulated by Dis3L2 to control proliferation, we used RNA-seq on dis3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…ZFC3H1-mediated condensation retention might have a more dominant role under such circumstances. In addition, mutations in exosome components have been associated with neurodevelopmental delay and intellectual disability ( 40 , 41 ). It would be interesting to examine whether polyA foci are formed in neurons of patients.…”
Section: Discussionmentioning
confidence: 99%
“…ZFC3H1-mediated condensation retention might have a more dominant role under such circumstances. In addition, mutations in exosome components have been associated with neurodevelopmental delay and intellectual disability ( 40 , 41 ). It would be interesting to examine whether polyA foci are formed in neurons of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Let-7a supplementation alone was previously shown to have no effect on AKT1 abundance [ 27 ]. Similarly, a recent study on HEK 293T cells showed that the deletion of DIS3L2 also results in increased phosphorylation of AKT at T308 [ 59 ]. Although TUT4/7 were previously suggested as chemotherapeutic targets, perturbation of uridylation-dependent RNA decay leads to potentially carcinogenic, increased AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 94%
“…RNA quality control and turnover are vital for cellular function, yet little is known about how nucleases deal with the diverse universe of structured RNAs. Dis3L2 is an RNAse II/R family 3’-5’ hydrolytic exoribonuclease that plays an important role in development and differentiation 1,7 , cell proliferation 811 , calcium homeostasis 12 , and apoptosis 13,14 by effectively removing or processing 3’ uridylated RNAs. Dis3L2 targets are oligo-uridylated by the terminal uridylyl-transferases (or TUTs) 1517 .…”
Section: Initial Binding Of Dis3l2 To Structured Substratesmentioning
confidence: 99%